2019
DOI: 10.55320/mjz.46.1.226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathological Profile of Patients with Prostate Cancer in Kampala, Uganda

Abstract: Background: Prostate cancer (PCa) is the most prevalent malignancy among adult men with marked variation in mortality rate across regions globally. Uganda has the highest incidence of prostate cancer in East Africa. This study explored the spectrum of clinical and histopathological profile of patients diagnosed with PCa in Uganda between 2012 and 2014 at the Department of pathology, Makerere College of Health Sciences (MakCHS). Methods: This was a descriptive cross-sectional study aimed at providing an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The above studies( [1,7,8,26] confirm with finding from other studies suggesting that Africans are likely to present with aggressive poorly differentiated prostate cancer unlike people from the white races [28], this could be is due to delayed hospital presentation however, African due to high testosterone levels and genetic predisposition are more likely to develop highly aggressive rapidly progressing prostate cancer [28].…”
Section: Rectal Examination In General Medical and Urology Clinics Ab...supporting
confidence: 86%
See 2 more Smart Citations
“…The above studies( [1,7,8,26] confirm with finding from other studies suggesting that Africans are likely to present with aggressive poorly differentiated prostate cancer unlike people from the white races [28], this could be is due to delayed hospital presentation however, African due to high testosterone levels and genetic predisposition are more likely to develop highly aggressive rapidly progressing prostate cancer [28].…”
Section: Rectal Examination In General Medical and Urology Clinics Ab...supporting
confidence: 86%
“…A study done by Yahaya at Mulago Mulago National Refferal Hospital Uganda in 2019, also revealed that a significant proportion of his patients 44.6% had a Gleason score of ≥ 8 [8] however still lower than the percentage determined by our study A South African study published in 2014 revealed that black South Africans presented with significantly more aggressive disease defined by Gleason score >7 and poorly differentiated tumor grade within rural versus urban localities [26]. Okuku during his retrospective review Makerere found that majority of the specimens had high-risk disease with a Gleason score of 9 or 10 in 66.7% of the patients.…”
Section: Rectal Examination In General Medical and Urology Clinics Ab...mentioning
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with findings by Nakandi et al [ 12 ] who reported poor knowledge, misconceptions, and poor PCa screening among adult men aged 18-71 residing in Kampala. Low uptake of PCa screening has been linked to multiple factors and barriers, such as lack of knowledge, low socioeconomic status, attitudes, and beliefs [ 12 , 16 ], and increases the risk of advanced disease [ 36 ]. KI interviews supported this finding where issues such as late screening and fears about screening impacted the uptake of PCa screening in Kazo.…”
Section: Discussionmentioning
confidence: 99%